Did Intimate Partner Violence Increase After the First COVID-19 Lockdown? A Study with Women Attending Antiviolence Centers in Italy - Romito, Patrizia; Laetitia, Marchand-Martin; Martina, Pellegrini; Marie-Josèphe , Saurel-Cubizolles (Italian Sociological Review, 2025)
Aim of the study is to analyze the evolution of intimate partner violence (IPV) after the first COVID-19 lockdown with women attending antiviolence centers (AVCs) in Italy. Of 292 women attending an AVC in 2020, 238 were victims of IPV; they were interviewed with a standardized questionnaire, including some open-ended questions. Questions concerned the evolution of violence after the lockdown; women’s fear; and socio-demographic variables. Women’s spontaneous comments were collected. Analyses focused on the increase in four types of violence: controlling behaviors and physical, sexual, and economic violence. After the lockdown, the evolution in violence was not uniform: for instance, physical violence increased for 22% of women and decreased for 55%, whereas controlling behaviors increased for 29% and decreased for 36%. In open-ended questions, women attributed this increase to the perpetrator’s need to regain control as after the lockdown, the women had regained some freedom. Cohabitation with the violent partner during the lockdown was the most important factor related to the increase in the four types of violence after the end of the lockdown. Most women were afraid of the perpetrator, particularly if they had cohabitated with the perpetrator during the lockdown: the increase in each type of violence was associated with women reporting fear. Women interviewed in this study reported high levels of partner’s violence and fear after the lockdown, particularly if they had cohabitated during the lockdown. Governments should provide the resources to prevent violence and support the victims; these measures must be included in post-Covid-19 recovery programs.